مقبیسٍ تبثیز یک ديرٌ فؼبلیت درمبودٌ سبس بز تؼبدل دیىبمیکی، تحزک پذیزی مفصل ي حس ػمقی مفصل مچ پبی سوبن دارای کف پبی صبف، گًد ي وزمبل. - مزیم مىبفی; سید صدر الدیه ضجب محمدػلی سلیمبن ف (Journal of Safety Promotion & Injury Prevention, 2022)
Background and Aim: The difference in altitude due to the foot's arch between people with normal and flat feet affects gait parameters and may increase risk of injury. Accordingly, this study aimed to compare the effect of exhaustive activity on dynamic balance (DB), joint mobility (JM), and joint proprioception (JP) in women with flat, hollow and normal feet. Methods: In this study, 30 participants were given a written informed consent form, and selected based on inclusion and exclusion criteria and the doctor's confirmation that the exercises were safe, and divided into two experimental groups of flat, hollow feet and a control group (10 participants in each group) by simple random sampling. The variables of the DB test (Y test), JM (goniometer), and JP (AutoCAD software) of the subjects in the pre-test stage were measured. After that, the group performed flat and hollow feet in exhaustive activity during one session. Results: The results showed that there was a significant difference between the pre-test and post-test of DB, JM, and JP of the subjects in the three groups. There is a significant difference between the mean difference of DB, JM, and JP of normal and hollow feet. But no significant difference was observed between the mean DB, JM, and JP of the experimental groups. Conclusion: Based on the results of this study, coaches in sports teams are recommended to improve the fatigue threshold in the athletes by designing appropriate programs and thus prevent injuries to the fullest extent.